CORTICAL VISION IMPAIRMENT - A CASE REPORT - Igor Isjanovski; Emilija Gosevska Dastevska (Faculty of Medicine, University Ss. Cyril and Methodius in Skopje, 2022)
Cortical visual impairment (CVI) is a brain-based visual impairment. The eyes can see, but the brain can’t interpret the visual world. Cortical visual impairment (CVI) in children is most commonly caused by peri- or postnatal hypoxia-ischemia, but may also occur following other insults, e.g., trauma, epilepsy, infections, drugs or poisons, and certain neurologic diseases. Case report: A case of a 9-year-old child, girl who was referred with Dg. epilepsy et CVI by a specialist doctor, pediatric neurologist from the University Pediatric Clinic for fundus examination and ophthalmological investigation and evaluation. Children with CVI have different levels of severity of visual impairment. There is no one-size-fits-all model, and every child is unique.